Influence of Seismic Loading on Segment Opening of a Shield Tunnel - Yang Chun-shan; Mo Hai-hong; Chen Jun-sheng; Wang Yi-zhao (The Scientific World Journal)
The influence of seismic loading on segment opening of a shield tunnel was explored using the dynamic finite element method to analyze the distribution of segment opening under multidirectional seismic loading, combined with a typical engineering installation. The calculation of segment opening was deduced from equivalent continuous theory and segment opening was obtained through calculations. The results show that the scope of influence of the foundation excavation on segment opening is mainly resigned to within 5 segment rings next to the diaphragm wall and 4 joints nearest the working well when the tunnel is first excavated followed by the working well in the excavation order. The effect of seismic loading on segment opening is significant, and the minimum increase of the maximal segment opening owing to seismic loading is 16%, while that of the average opening is 27%. Segment opening under bidirectional coupled seismic loading is significantly greater than that under one-dimensional seismic loading. On the basis of the numerical calculations, the seismic acceleration and segment opening caused by seismic action were normalized, and a new calculation method was proposed for predicting the maximal segment opening of a shield tunnel at different depths under conditions of seismic loading.